2021
DOI: 10.1038/s41589-021-00831-5
|View full text |Cite
|
Sign up to set email alerts
|

HUWE1 employs a giant substrate-binding ring to feed and regulate its HECT E3 domain

Abstract: HUWE1 is a universal quality-control E3 ligase that marks diverse client proteins for proteasomal degradation. Although the giant HECT enzyme is an essential component of the ubiquitin-proteasome system closely linked with severe human diseases, its molecular mechanism is little understood. Here, we present the crystal structure of Nematocida HUWE1, revealing how a single E3 enzyme has specificity for a multitude of unrelated substrates. The protein adopts a remarkable snake-like structure where the C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…To further test the utility of LotA N in diagnosing the presence of K6 linkages among a complex mixture, we generated polyUb chains with HUWE1, a human HECT E3 ligase that is reported to assemble a mixture of K6-, K11-, and K48-linked chains (Michel et al , 2017; Jäckl et al , 2018; Grabarczyk et al , 2021). Treatment with the K11-specific DUB Cezanne released the largest amount of monoUb, followed by the K48-specific OTUB1*, then LotA N , and finally the constitutively-activated K63-specific AMSH* (Michel et al , 2015), which had only a marginal amount of activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further test the utility of LotA N in diagnosing the presence of K6 linkages among a complex mixture, we generated polyUb chains with HUWE1, a human HECT E3 ligase that is reported to assemble a mixture of K6-, K11-, and K48-linked chains (Michel et al , 2017; Jäckl et al , 2018; Grabarczyk et al , 2021). Treatment with the K11-specific DUB Cezanne released the largest amount of monoUb, followed by the K48-specific OTUB1*, then LotA N , and finally the constitutively-activated K63-specific AMSH* (Michel et al , 2015), which had only a marginal amount of activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that a conformational switch regulates HUWE1 activity (Sander et al, 2017). Recently, cryo-EM structures of Nematocida and human full-length HUWE1 demonstrated that HUWE1 harbors a snake-like and giant substrate-binding ring, which is highly dynamic, enabling engagement with a multitude of diverse substrates for catalysis via the flexible HECT domain (Hunkeler et al, 2021;Grabarczyk et al, 2021). The HUWE1 protein has become an attractive potential therapeutic target for treating cancer and other diseases, and structural analysis will significantly advance the development of activity inhibitors with substrate-selective recruitment.…”
Section: Huwe1 Activity Regulation and Perspectivesmentioning
confidence: 75%
“…Due to its large size, the HUWE1 protein has been identified to mediate the ubiquitination of a multitude of diverse substrates through its giant substrate-binding ring structure, and this ring structure is highly dynamic. The ligase activity of the flexible C-terminal HECT domain is actually determined by its conformational change through dimerization of the C-terminal HECT domain or disruption of the dimer interface (Sander et al, 2017;Grabarczyk et al, 2021;Hunkeler et al, 2021). Furthermore, Huwe1 gene is located on the X chromosome and associated with X chromosome-linked intellectual disability.…”
Section: Ubiquitination and E3 Ligasesmentioning
confidence: 99%
“…Previous studies have indicated that HUWE1 can target broader classes of cellular substrates (Hunkeler et al , 2021; Grabarczyk et al , 2021), but that the targeted proteins may be cell type specific to some degree. Analysis of proteome changes in the three different cell lines identified seven proteins that were consistently increased in all Huwe1 -targeted cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%